INVESTOR IRRATIONALTY IN THE INDONESIA CAPITAL MARKET : AN EMPIRICAL STUDY OF STOCKS LISTED ON THE IDX - Regina Hingi66 Hayong; I Wayan Widnyana (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2025)
This study aims to identify and analyze irrational investor behavior in the Indonesia capital market, specifically in companies listed on the Indonesia Stock Exchange (IDX). Unsing a quantitative approach and secondary data from 2020-2023, this study examines the influence of behavioral biases such as overconfidence, herding and loss aversion on stock returns. The results indicate that psychological biases significantly influence investmen decisions, confirming that investorts on the IDX do not always act rationally as assumed by efficient market theory.